The effect of diabetes on complications after distal pancreatectomy : A population-based cross-matched registry study - Bergenfeldt, Henrik; Ekström, Eva; Fagher, Katarina; Filipsson, Karin; Andersson, Bodil ; 0000-0001-5591-0659 (Scandinavian Journal of Surgery, 2025)
Background: Distal pancreatic resection is associated with a high frequency of postoperative complications. The aim of this study was to characterize the effect of diabetes mellitus (DM) on short-term complications after distal pancreatectomy. Methods: Patients who underwent distal pancreatectomy between 1 January 2010 and 31 December 2020 were identified from the Swedish National Pancreatic and Periampullary Cancer Registry, and the data were cross-linked with the National Diabetes Registry. The complication rates were compared between patients with and without diabetes. Results: In total, 1297 patients underwent distal pancreatectomy, and 247 (19%) of these patients had DM. Postoperative complications occurred in 697/1297 (54%) patients. There was no difference observed in the risk of overall complications (odds ratio (OR) = 0.76, 95% confidence interval [CI]: 0.58–1.00; p = 0.052), general surgical complications (p = 0.053), medical complications (p = 0.872), or postoperative pancreatic fistula rates (p = 0.603) according to the univariable analysis. In the multivariable analysis, patients with DM demonstrated a lower risk of overall complications (OR = 0.72, 95% CI = 0.54–0.96; p = 0.025). In the subgroup analysis, patients with high mean HbA1clevels (p = 0.041), high last measurement (p = 0.032), or DM duration >10 years (p = 0.022) exhibited lower risks of complications in the multivariable analysis. Conclusion: This study revealed a lower overall complication risk in patients with DM compared to patients without DM after distal pancreatectomy; however, no difference in the pancreatic fistula rate or medical complications was observed.
Keywords: diabetes mellitus; Distal pancreatectomy; hepatobiliary surgery; pancreatic cancer; pancreatic surgery; surgical complications